Osteointegration of hydroxyapatite- coated collars in cemented massive endoprostheses following revision surgery. (2021) - Davies, B.; Kaila, R.; Andritsos, L.; Stephens, C. Gray; Blunn, G. W.; Gerrand, C.; Gikas, P.; Johnston, A.
No abstract available